Pengaruh kepemimpinan transaksional terhadap komitmen dimediasi oleh kepuasan kerja - Imam Syafi'i; Endi Sarwoko (MBR (Management and Business Review), 2018)
The purpose of the study was to analyze the effect of transactional leadership on commitment mediated by job satisfaction. The sample used to be employees of the Krebet Baru Malang PG Company, as many as 62 people, data were collected using a questionnaire, and the data analysis technique used Path Analysis. The results showed that transactional leadership had a positive and significant effect on commitment, transactional leadership had a positive and significant effect on work commitment which was mediated by job satisfaction in Krebet Baru PG Malang. The result findings show that transactional leadership plays a role in increasing organizational commitment, while also contributing to increasing job satisfaction, job satisfaction will have an impact on organizational commitment.